Perkembangan Politik Ditinjau Dari Agama Mulai Nabi Muhammad Sampai Abad Pertengahan - Moh Mustaqim (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
Islam is the most intact religion, it not only concerns about spirituality but also teaches many things in it, the most complex problems that become human problems besides religion, economics and some other social activities are the state, the state becomes very important for discussed because basically the state becomes the container or the main point of running the routine of life. various policies, laws, politics and government systems in a country will greatly determine the progress and benefit of its people.The problem with the success of the leadership system has always been the most exciting issue in history. In addition to the emergence of the problem of power struggles and power, the problem of empowering people and maintaining civilization is also one of the keys to the transition of power. One of the most well-known leadership successions in history is that the succession took place after the death of the Prophet Muhammad SAW.